NUDT15 Polymorphism Confer Increased Susceptibility to Thiopurine-Induced Leukopenia in Patients With Autoimmune Hepatitis and Related Cirrhosis - Fan, Xiaoli; Yin, Dandan; Men, Ruoting; Xu, Heng; Yang, Li (Frontiers in Pharmacology, 2019)
The aim of this study was to investigate the influence of NUDT15 R139C and thiopurine S-methyltransferase (TPMT) on azathioprine (AZA) induced leukopenia in patients with autoimmune hepatitis (AIH) and related cirrhosis. A total of 149 Chinese AIH patients with a history of AZA treatment were retrospectively evaluated. The clinical and epidemiological characteristics of the patients were obtained from an electronic database and reviewed. NUDT15 (rs116855232) and TPMT∗3C (rs1142345) SNPs were genotyped using a PCR method. Twelve patients developed leukopenia, and this adverse drug reaction was significantly associated with the T risk allele in NUDT15 [P < 0.00001, odds ratio = 20.41; 95% confidence interval (CI) (7.84, 53.13)], with the sensitivity and specificity of 91.67 and 89.05%, respectively. The median maintenance dosages for patients with the rs116855232 CC and CT genotypes were 1.23 (0.95, 1.53) mg ⋅ kg−1 ⋅ d−1 and 0.96 (0.83, 1.19) mg ⋅ kg−1 ⋅ d−1, respectively (P = 0.028). In contrast, no significant association was observed for TPMT∗3C genotypes. Notably, subgroup analysis of the 13 patients with leukopenia before therapy, these white blood cell (WBC) counts did not show further reduction after AZA treatment and maintenance dosage was 1.13 (0.94, 1.60) mg ⋅ kg−1 ⋅ d−1. Therefore, NUDT15 polymorphism is significantly associated with thiopurine-induced leukopenia in Chinese patients with AIH and related cirrhosis. Adjusting the AZA dosage should be considered in patients according to the NUDT15 R139C genotypes.